The national health insurance scheme in Ghana: Implementation challenges and proposed solutions - Gajate-Garrido, Gissele; Owusua, Rebecca (International Food Policy Research Institute, 2013)
Healthcare financing through social health insurance has become a very important tool in providing access to and utilization of health services in most developing countries such as Ghana. Ghana’s National Health Insurance Scheme (NHIS) is a promising tool for policymakers. Yet since its inception in 2003, few studies have assessed the scheme. This paper aims to explore the challenges facing the District Mutual Health Insurance Schemes (DMHISs), how these challenges have been managed over the years, and what can be done to improve the DMHIS operation. The scope of this study is to improve policies and guide support for Ghanaian DMHISs as well as to provide recommendations when implementing future NHISs in a developing-country context.